Estimated global and regional economic burden of genital herpes simplex virus infection among 15-49 year-olds in 2016 - Nathorn Chaiyakunapruk; Shaun Wen Huey Lee; Puttarin Kulchaitanaroaj; Ajaree Rayanakorn; Haeseon Lee; Katharine Jane Looker; Raymond Hutubessy; Sami L. Gottlieb (BMC, 2024)
Abstract Background Globally, herpes simplex virus (HSV)-2 and -1 infections contribute to a large disease burden, but their full economic consequences remain unclear. This study aims to estimate the global economic impact of genital HSV-2 and HSV-1 infection and its consequences for people with genital ulcer disease, neonatal herpes, and human immunodeficiency virus (HIV) infection attributable to HSV-2. Methods Using a societal perspective, the economic burden was calculated at the country level and presented by World Health Organization (WHO) regions and World-Bank income levels. The disease burden was obtained from previously published global disease burden studies in 2016 and disaggregated for 194 countries. Estimates of healthcare resource utilisation were sourced from a literature review, and online interviews were conducted with 20 experts from all 6 WHO regions. Relevant costs were obtained from the literature and estimated in 2016 international dollars (I$). Results Both genital HSV-2 (I$31·2 billion) and HSV-1 (I$4·0 billion) infections and their consequences were estimated to cost I$35·3 billion globally in 2016. The major economic burden was from the Americas and Western Pacific regions combined, accounting for almost two-thirds of the global burden (I$20·8 billion). High- and upper-middle-income countries bore a large proportion of the economic burden (76·6% or I$27·0 billion). Costs were driven by the large number of HSV-2 recurrences; however, even assuming conservatively that people with symptomatic herpes have on average only one episode a year, global costs were estimated at I$16·5 billion. Conclusions The global costs of genital HSV infection and its consequences are substantial. HSV prevention interventions have the potential to avert a large economic burden in addition to disease burden; thus, efforts to accelerate HSV vaccine development are crucial.